Nordihydroguaiaretic acid, a cytotoxic insulin-like growth factor-I receptor/HER2 inhibitor in trastuzumab-resistant breast cancer - Rowe, Danica L; Ozbay, Tuba; Bender, Laura M; Nahta, Rita (Molecular cancer therapeutics, 2008)
The majority of patients with HER2-overexpressing metastatic breast cancer who initially respond to the HER2-targeted antibody trastuzumab show disease progression within 1 year. The identification of novel agents that effectively inhibit survival of cancer cells that have progressed on trastuzumab is critical for improving outcome for this patient population. In the current study, we show that the phenolic compound nordihydroguaiaretic acid (NDGA) promoted cell death of trastuzumab-naive and trastuzumab-refractory HER2-overexpressing breast cancer cells. NDGA induced DNA fragmentation, cleavage of poly(ADP-ribose) polymerase and caspase-3, and inhibition of colony formation. In addition, NDGA inhibited insulin-like growth factor-I and HER2 signaling in trastuzumab-refractory cells, with reduced downstream phosphatidylinositol-3 kinase/Akt signaling. Importantly, combination treatment with NDGA and trastuzumab suppressed proliferation and survival of trastuzumab-refractory cells to a greater degree than either agent alone, suggesting that NDGA increases the sensitivity of refractory cells to trastuzumab. Derivatives of NDGA are currently in clinical trial for other solid tumors. Our data strongly support further study of NDGA as a potential therapeutic against breast cancers that have progressed on trastuzumab.